Effectiveness of level two anomaly ultrasound scan for detection of congenital anomalies - an observational retrospective study - Alka S Gupta; Geeta S Kulkarni; Suraj D Bhame (New Indian Journal of OBGYN)
Objectives: This study was done to find the effectiveness of level two anomaly scan in detection of congenital anomalies and also to find the maternal and neonatal factors associated with congenital anomalies. Methods: Pregnant women with gestational age of more than or equal to 18 weeks were included in the study. All participants were recruited when they went into labour. At the delivery of live baby, stillborn baby, abortion or after medical termination of pregnancy, the neonate/abortus was examined and all the details were recorded and analyzed. Results: The proportion of anomalies detected on level two anomaly scan was 7.33% and the proportion of babies with congenital anomalies was 7.16% (n=43). The sensitivity of level two anomaly scan in detecting anomalies was 74.41% and its specificity was 97.84%. The positive predictive value of level two anomaly scan was 72.72% and its negative predictive value was 98.02%. Percentage of false negatives was 25.58% while the percentage of false positives was 2.15%. Anomalies of the central nervous system were the most commonly found anomalies (33.92%) while respiratory system accounted for the least number of all anomalies (1.78%). Congenital diaphragmatic hernia was the single most common anomaly. There was a significant difference (p<0.05) between presence of congenital anomalies and extremes of maternal ages (weak association, CC=0.159, OR=3.7), consanguineous marriages (moderately strong association, CC=0.292, OR=9.96) and between patients who did not take folic acid supplements in the first and second trimester (weak association, CC=0.113, OR=3.14). Babies with congenital anomalies have higher chances of having malpresentations (association not appreciable, CC=0.088, OR=2.9). Pregnancies with anomalous babies had significant chances of having amniotic fluid volume changes (moderate association, CC=0.279, OR=13.08). The association with having oligohydramnios was stronger (CC=0.238, OR=1.2) than in those having polyhydramnios (CC=0.119, OR=10.3). Congenital anomalies significantly increased neonatal mortality rates (strong association, CC=0.339, OR=18.94) and perinatal mortality rates (Strong association, CC=0.353, OR=16.18). Conclusion: Level two anomaly scan should be offered to all antenatal mothers and should be used for diagnosis in antenatal period so that preventive measures can be implemented especially in the high risk population.